(3CKQ GdGYdGf Yf GdGQHGM aj Sdhc GdeSJKeQjf HGdGJLGQ HGdGSge (B:s (3OQGSI JMdjdjI Yf GdTQcGJ GdeSLdI aj HhQUI YeGf ddaJQI (B2001 (3`` (B2005 /s - (3GdYHO GddGJ, MSGe GHQGgjes ((3YeGf(B: s (3OGQ jGaG GdYdejI ddfTQ hGdJhRjY(B, s, 2010)
(3Yde GdfaS hGdCShGb GdeGdjI, GdEYdGfGJ Yf GdCQHGM aj GdLGfH GdfXQj aj GdJTQjYGJ GdCQOfjI, GdWHjYI GdYThGFjI ddJZjQGJ aj GdCQHGM, GdJbGQjQ GdeGdjI cCOGI EJUGd eY GdCShGb GdeGdjI, GSJLGHGJ MLe GdJOGhd ddEaUGM GdeMGSHj, GdeMJhi GdeYdheGJj ddUabI GdJLGQjI aj CShGb GdChQGb GdeGdjI, GdeYdheGJ hcaGAI GdShb, GdaYGdjI Ydi eSJhi GdVYja hTHg Gdbhj hGdeSJhi Gdbhj, fJGFL GdOQGSIs
(3bGFeI GdLOGhd U(B.13s
Keywords: (3GdGQHGMs; (3GdGSJKeGQ `` YeGfs; (3GdGYdGfs